The Making of Music Venues: Inquiries into Global Urban History. (September 2021) - Escher, Cornelia; Rempe, Martin
Music venues form nodal points around which to explore networks of people and the materialization of styles, trends, and ideas. Moreover, they work as condensers, bringing together the domain of aesthetic experience with social, political, and economic factors. Our special section takes these observations as a starting point to study these particular urban spaces, with a special focus on the first half of the long twentieth century. By highlighting agency, the interplay between music and architecture, and the human experience and use of music venues, we will address the making of such venues and their entanglement with urban cultures. Examples include a wide range of venues that provided high culture as well as mass entertainment in Nashville, Montreal, Ankara, and Havana. On a methodological level, the section broadens the field of urban history and at the same time points to some empirical limits of a global urban history. The focus on music venues thus serves as a means to inquire into the transformations of taste, experience, agency, and style in urban cultures, which, in some respects, withstand a "global" explanation.